지각된 온라인쇼핑몰속성이 신뢰,몰입,구매의도에 미치는 영향에 관한 연구 - 김현철(Hyun-Chul Kim) (한국컴퓨터정보학회논문지, 2018)
This study presents perceived reputation, perceived quality, perceived assurance of online shopping malls as the attributes factors of online shopping malls and identifies the impact of perceived online shopping mall attributes on trust, involvement and purchasing intention. Also we analyzed whether trust on online shopping mall affect involvement and purchasing intention, and whether involvement on online shopping mall affect purchasing intention. The results show that perceived quality, perceived assurance of online shopping malls influence positively on trust, but perceived reputation does not. Second, perceived reputation, perceived quality, perceived assurance of online shopping malls doesn’t influence positively on involvement. Third, perceived quality, perceived assurance of online shopping malls influence positively on purchasing intention, but perceived reputation does not. Forth, trust on online shopping mall influence positively on involvement and purchasing intention. Fifth, involvement on online shopping mall influence positively on purchasing intention. KCI Citation Count: 0